Low‐carbon scheduling model of multi‐virtual power plants based on cooperative game considering failure risks - Chen Wu; Zhinong Wei; Yang Cao; Yiteng Xu; Tiantian Wei; Haiteng Han; Sheng Chen; Haixiang Zang (IET Renewable Power Generation)
Abstract The increasing amount of distributed renewable energy (DRE) is participating in grid‐connected operation as an important unit of the virtual power plant (VPP) aggregation. VPP also contains a variety of flexible resources such as demand response (DR), energy storage (ES), and fuel cell (FC). How to achieve efficient energy utilization while reducing carbon emissions and resisting the risk of failure caused by extreme weather has attracted widespread attention. In this article, a cooperative game‐based low‐carbon scheduling model for multi‐VPPs under the consideration of typhoon‐induced grid outage risks is proposed. First, a cooperative game mechanism for multi‐VPPs is constructed. And a bi‐level model of multi‐VPPs low‐carbon scheduling is built under the framework of electricity‐carbon trading markets. Second, the bi‐level scheduling model is linearized based on the Strong Duality Theorem and Karush‐Kuhn‐Tucker (KKT) condition. Then, the dispatch scheme of each VPP under the cooperative game form is obtained. Finally, simulations are performed to verify the validity of the proposed model. The results show that the economic and low‐carbon performance of multi‐VPPs can be improved by applying the cooperative game, which can also enhance the power system ability of resisting line faults.